PERFORMING (IN)JUSTICE: THE CONTENTIOUS POLITICS OF DIGITALLY MEDIATED VISUALS - Lewis, Kelly; Berents, Helen; Myles, David; Cabalquinto, Earvin Charles; Matamoros Fernández, Ariadna; Estrada-Grajales, Carlos (AoIR Selected Papers of Internet Research, 2019)
This panel considers sociopolitical contentions as being increasingly visually mediated and brings together a transdisciplinary group of researchers to reflect on the complex ways digitally mediated visuals construct, sustain and perform (in)justice. To do this, panelists reflect on the many forms and political textures digitally mediated visuals can assume (online and offline), and considers the specific role of digital affordances and platform politics in sustaining these practices. Panelists address key questions: 1) how do digitally mediated visuals enact forms of (in)justice?; 2) what potentials or limitations do digitally mediated visuals generate for scholars wishing to understand broader sociopolitical contentions?; and 3) what conceptual and methodological tools should (Internet) scholars employ to study the contentious politics of digitally mediated visuals (and with what ethical implications)? Drawing from media and communication, international relations, cultural studies and discourse theory, panelists address a variety of sociopolitical topics across platforms (WhatsApp, Instagram, Facebook and Twitter) and territories, including: US black justice movements, sexual racism in Latin America and Southeast Asia, conflicts over representations of death in the Middle East, and transnational movements for trans rights activism. Panelists engage with Internet research to investigate the contentious politics of digitally mediated visuals by drawing on several perspectives to challenge hegemonic conceptions, Western biases and dominant discourses. They also mobilize qualitative or hybrid methods to track the trajectories of digitally mediated visuals to understand their biographies and sociopolitical productiveness in the context of their emergence, methods particularly interesting for Internet studies considering ongoing critiques against big data approaches.